Seasonal Variation in Avian Fauna of Sarsuna Satellite Township Area – A Case Study - Saha, Indraneel; Dey, Suvajit; Palit, Swagata (International Journal of Scientific Research in Biological Sciences, 2022)
Birds are considered as one of the most significant indicators of the environment. Because they are very much sensitive to habitat change. Changes in bird populations are an important indication of environmental problems. During the time of urbanization, the population of birds has been particularly affected mainly in urban and suburban areas. The area of our study – Sarsuna Satellite Township is mainly a suburban region where the bird population is also likely to be affected. However, our study mainly focuses on the analysis of these bird populations and to compare their diversity indices in pre and post monsoon season. The study reveals a wide range of birds according to their feeding habits and their family. A comparative study summarizes that there is no significant difference in bird diversity between two seasons but however the total bird count irrespective of the seasons are alarmingly low and therefore need special attention.